2019
DOI: 10.1186/s13041-019-0466-z
|View full text |Cite
|
Sign up to set email alerts
|

Absence of BBSome function leads to astrocyte reactivity in the brain

Abstract: In humans, dysfunctional primary cilia result in Bardet-Biedl syndrome (BBS), which presents with clinical features including intellectual disabilities, obesity, and retinal degeneration, and, in mouse models, the added feature of hydrocephalus. We observed increased Glial Fibrillary Acidic Protein (GFAP) immunoreactivity in BBS mouse brains. Increased GFAP expression is a hallmark of astrocyte reactivity that is associated with microglia activation and neuro-inflammation. To gain a better understanding of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Consistent with previous study 1 , we found that serpinA3N expression was upregulated at 6-12 h after reperfusion and lasted for This was controversial with the previous belief that serpinA3N was a marker of reactive astrocytes 1 . Although most reported the expression of serpinA3N in reactive astrocytes in various models, 14,15,41 two recent studies revealed serpinA3N expression in neurons in schizophrenia model 42 and in oligodendrocytes in Alzheimer's disease (AD). 43 We are the first to report serpinA3N cellular distribution in stroke model.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous study 1 , we found that serpinA3N expression was upregulated at 6-12 h after reperfusion and lasted for This was controversial with the previous belief that serpinA3N was a marker of reactive astrocytes 1 . Although most reported the expression of serpinA3N in reactive astrocytes in various models, 14,15,41 two recent studies revealed serpinA3N expression in neurons in schizophrenia model 42 and in oligodendrocytes in Alzheimer's disease (AD). 43 We are the first to report serpinA3N cellular distribution in stroke model.…”
Section: Discussionmentioning
confidence: 99%
“…Cilia defects can trigger inflammation in the kidney and in the brain [34,35]. Moreover, Urotensin II signaling induces inflammation in many contexts [36], raising the interesting possibility that increased URP signaling from CSF-cNs could drive neuroinflammation in the rpgrip1l ∆/∆ zebrafish scoliosis model.…”
Section: Discussionmentioning
confidence: 99%
“…In order to control for these phenotypes, we used young adult mice prior to the onset of obesity and blindness. In addition, our BBS1 conditional knockout mice are not blind nor obese and BBS8 conditional knockout mice do not have hydrocephalus [ 20 , 51 ], yet both models have impaired long-term context fear conditioning. We were not able to account for the olfactory deficit as a confounding factor.…”
Section: Discussionmentioning
confidence: 99%